Effect of alkoxy-spacer length and solvent on diluted solutions of cationic isothiouronium polythiophenes - Dominguez SE; Merilainen M; Aaritalo T; Damlin P; Kvarnstrom C (ROYAL SOC CHEMISTRY, 2025)
This contribution presents a study on two cationic isothiouronium polythiophenes (poly-3-(N, N-diethyl-S-iso-thiouronium) alkoxy-4-methyl thiophene), with alkoxy chains of different length in the 3-position of the thiophene ring, results of steady-state absorption and fluorescence spectroscopies in four solvents of different polarities: protic water, protic-protic water-isopropanol, protic-aprotic water-tetrahydrofuran and protic-non polar water-1,4-dioxane (all mixtures 0.5 v/v) are presented. Molar absorption coefficient (epsilon), quantum yield (phi(f)), spectral maxima (lambda(max), lambda(em)) and Stokes shift (Delta nu) are presented, and the effect of solvents on these parameters is discussed. Empirical optical and electrochemical energy levels were estimated using drop cast films on glass and on glassy carbon electrode, respectively. Density functional theory was used to gain supporting structural, energy and electronic information of different oligomers, simulating solvents of different polarity.